Analisis Kluster Kejadian Stunting pada Balita di Provinsi Kalimantan Timur - Ros diana Tasman; Arief Wibowo; Rachmah Indawati; Alinea Dwi Elisanti (Jurnal Kesehatan, 2020)
Malnutrition is still a major problem in Indonesia. Stunting (short stature) is a form of malnutrition in which a very short and short stature exceeds a 2 SD deficit below the median length or height of the population. The prevalence of short and very short toddlers nationally according to Riskesdas 2018 reaches 30.8%. The incidence of stunting in East Kalimantan Province in 2017 reached 30.86%, but there is no area categorization based on the prevalence of stunting in each Public Health Service (PHS). It is need to conduct the reseacrh to cluster the incidence of stunting based on other health parameters. The unit analysis of this study was 187 PHS in East Kalimantan Province, the data source was obtained from the Health Profile of the East Kalimantan Province, the data analysis used K-mean cluster with alpha 5%. The determination of the cluster is based on the incidence of stunting, LBW, Exclusive Breastfeeding and Complete Basic Immunization (CBI) in East Kalimantan Province. The results showed that there were 3 PHS clusters in East Kalimantan Province. Cluster 1 consists of 77 PHS with low incidence rates of stunting and LBW of 18.1% and 7.13%, cluster 2 consists of 109 PHS with low rates of stunting and LBW namely 8.04% and 2.7%, while cluster 3 consisted of 1 PHS with incidence of stunting, LBW and CBI above the total average, namely 15.2%, 12.5% and 323.8%. The highest incidence of stunting is at PHS Cluster 1 wich having a low coverage of Exclusive breasfeeding and CBI. It is more influenced by the topography of the Kutai Kartanegara area, where several areas are located on the coast and inland so the health workers get difficulties in accessing the community because they have to be reached by sea, river and lake.